The Stereopsis Ability Based on Corrected Refractive Errors in School-Age Children - Indrajanti, Mirza; Silaen, Desi Hartati; Hasan, Hasan (Jurnal MedScientiae, 2025)
Stereopsis is the highest binocular vision ability which is very important in children's visual development. Especially in supporting the learning process and daily activities. Refractive disorders such as myopia, hypermetropia, and astigmatism that are not properly corrected can inhibit the development of stereopsis. Objective: To determine the stereopsis ability based on the type of refractive disorder that has been corrected in students of SDN 11 Pagi and SDN 17 Kebon Jeruk in 2025. Method: This study used a quantitative descriptive design with a cross-sectional approach. The sample consisted of 792 students who had their refractive disorders corrected and met the inclusion criteria. Results: Of the total 792 students, 465 students had refractive disorders, with the highest proportion of compound myopic astigmatism (27.9%). This group also showed the highest percentage of subnormal stereopsis (33.5%). In addition, of the 115 students with subnormal conditions, many (51.3%) were accompanied by anisometropia. Conclusion: There are differences in stereopic abilities in children based on corrected refractive errors, groups with a combination of refractive errors accompanied by anisometropia mostly experience subnormal stereopsis. Therefore, it is important to do early detection and correct refractive errors appropriately to support the development of binocular vision and children's learning achievements so that they are maximized.